Vulnerability to and perception of climate change among small-scale fishing communities from the South Brazil Bight - Martins, Ivan Machado (2018)
Fishing is one of the main extractive activities of marine resources and constitutes an important source of food, income and livelihood for millions of people around the world. Fishing communities are highly susceptible to economic, social, natural and climate changes. Climate change has affected the livelihoods of fishing communities, and the impacts and consequences are still poorly understood. Therefore, this thesis sought to provide a better understanding of the impacts of climate change on small-scale fishing communities, using an analytical approach focusing on perception and vulnerability. The study area was the South Brazil Bight region, defined as the continental shelf area that extends between Cabo Frio (RJ) and Cabo Santa Marta (SC). The region has unique characteristics, as it is located in the most urbanized and industrialized region of the country and has several small- and large-scale fishing communities. To represent the diversity of the fishing communities in the region, 8 communities with distinct characteristics were selected: Itaipu (RJ), Ilha do Araújo (RJ), Enseada (SP), Bonete (SP), Boqueirão Sul (SP), Mandira (SP), Pontal de Leste (SP) and Praia do Porto (SC). A total of 151 households were interviewed in the selected communities from November 2014 to September 2016. In the first chapter of this thesis, an ethno-oceanographic approach was applied to investigate fisher perceptions on climate and ocean changes and the impact of such changes on fisher livelihoods. The results show that fishers detected changes in the environment and that these changes are positively and negatively impacting their yields and livelihoods. In the second chapter, a cross-scale approach was used to assess and identify the key factors that affect the vulnerability of fishing communities to climate change. Among the vulnerability factors, the distance to the market and urban centers and the lack of institutional support increase fishing community vulnerability to climate change; community organization, strong leadership, partnership with researchers, co-management and livelihood diversification reduce the vulnerability of communities. In the third chapter, the vulnerability approach was used again but at the regional level, by comparing data from the South Brazil Bight with the southern Cape of South Africa. Among the factors that differentiate the two regions, a high dependence on fishing, a strong attachment to place, and the lack of policy focused on small-scale fisheries increase the vulnerability of the communities in the South Brazil Bight, while participation in the decision-making process, ownership of boats and fishing rights are factors that reduce the regional vulnerability of the South Brazil Bight. Therefore, these findings provide a better understanding of the impact of climate change on the livelihood of fishers and fishing communities and serve as a basis for the development of effective climate change adaptation strategies that have minimal social impacts.